UMAR IBN AL-KHATTAB’S VISITS TO BAYT AL-MAQDIS: A STUDY ON ITS REASONS AND OBJECTIVES - Al-Tel, Othman Ismael; Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2017)
The aim of this paper is to examine historical accounts relating to Umar Ibn al-Khattab's visit to Bayt al-Maqdis, by focusing on the reasons, aims and objectives. Multiple historical sources with diverse accounts have posed a challenge to modern researchers in determining the accuracy and validy of issues surrounding Umar's visit to Bayt al-Maqdis. Therefore in this paper the authors gather all the available reasons, compare them and try to link them with the surrounding situation. At the same time, the authors provide explanations of the reasons for the great contradictions among the Islamic sources and accounts. In addition, the reasons behind the different visits of Umar's to Syria and the work he carried out in each visit is reported and explained. Through the analysis of the early sources, the authors also discuss and analyse the views of some modern researchers who have dealt with this issue.